Searching for Sex Trafficking Victims: Using a Novel Link-Tracing Method Among Commercial Sex Workers in Muzaffarpur, India. (December 2021) - Vincent, Kyle; Zhang, Sheldon X.; Dank, Meredith
Estimating the prevalence of sex trafficking requires a practical sampling strategy to reach the hidden population. In this study, we experimented with a network sampling design to obtain a sample of sex workers from the city of Muzaffarpur, India. Backed by census data and other auxiliary information, we obtained a stratified initial sample of 111 individuals and with two waves of referrals arrived at a final sample of 317 individuals. A sophisticated network-based approach is used to estimate the population size, and a respondent-driven sampling–based strategy is used to estimate characteristics related to sex trafficking violations. We detail the sampling design and present results from the study, highlighting significant findings and lessons learned that can be used for future studies.